Tax System and Conditioning of Business Environment in Lithuania - Rutkauskas, Aleksandras Vytautas; Tvaronaviciene, Manuela (Ekonomika, 2000)
In this article an officially declared direction of a future tax reform is discussed. The main emphasis is put on the examination of a role of a profit tax in conditioning of contemporary economical environment of operating business firm and impact of consumption taxes on a behavior of various participants of market. International practice of imposing a profit tax and a value added tax (VAT) is considered and international comparisons are made. The article argues for introducing a progressive profit tax and reducing value added tax.